Encryption of Photos: Protecting Privacy and Securing Sensitive Images - Nadya Musbah Mohamed Almannouni (African Journal of Advanced Pure and Applied Sciences, 2024)
One popular and extremely secure encryption algorithm is called Advanced Encryption Standard (AES). In 2001, the Data Encryption Standard (DES) was replaced by the National Institute of Standards and Technology (NIST). AES allows key sizes of 128, 192, and 256 bits and runs on set block sizes. It offers strong security, effective performance, and flexibility through the use of a substitution-permutation network (SPN) architecture. Virtual private networks (VPNs), wireless communication, network security, and data protection are among the fields in which AES finds use. Because it is widely used and standardized, it is an essential instrument for guaranteeing secure communication and data secrecy across various industries.